Surveillance for African Swine fever in Nigeria, 2006-2009 - Fasina, F.O.; Shamkai, D.; Makinde, A.A.; Lombin, L.H.; Lazarus, D.D.; Rufai, S.A.; Adamu, S.S.; Agom, D.; Pelayo, V.; Soler Garzón, Alvaro; Simon, A.; Adedeji, A.J.; et al. (Wiley, 2010)
African swine fever (ASF) has had significant economic and social impact in Nigeria since 1997. However, there has been no effective national response to bring it under control. In this report, we confirm that ASF is still prevalent and widespread in Nigeria. Results from both serosurveillance and virological analyses indicated that ASF is present in most of the agro-ecological zones of the country. Nine per cent (9%) of serum samples and 48% of tissue samples were positive for ASF virus antibody and genome, respectively. Areas with high pig-related activities (marketing, consumption and farming) have higher prevalences compared with areas with less pig activities. Farm-gate buyers, marketing systems and transport of untested pigs within the country assist with the circulation of the virus. Only by putting in place a comprehensive routine surveillance and testing system, reorganizing the market and transportation systems for pigs, implementing on-farm bio-security protocols and considering the option of compensation will it be possible to achieve a significant reduction in ASF prevalence in Nigeria.